SOCIO-ECONOMIC COOPERATION OF THE SHANGHAI COOPERATION ORGANIZATION COUNTRIES - Nigmatov Alisher Khayrullayevich (Western European Studies, 2024)
This article deals with the socio-economic cooperation of the countries of the Shanghai Cooperation Organization. Its historical formation and the factors contributing to this are given. In addition, it is possible to know that the socio-economic cooperation of the Shanghai Cooperation Organization is of great importance at the present time.
Keywords: Shanghai; summit; Almaty; economy